The Guided Note-Taking Method Assisted by Video Media on Science Learning Outcomes in Society Era 5.0 - Aricha Sharaswati; Achmad Fathoni (Universitas Pendidikan Ganesha, 2022)
Elementary school students' low science learning outcomes are caused by a lack of student interest in learning, students' laziness in taking notes, and the lack of media that supports learning in class. This study aimed to analyze the Guided Note Taking method assisted by video media on the success of students' scientific learning in human hearing material. This study uses a quantitative experimental research method, namely a quasi-experimental design. Data collection instruments use documentation, questionnaires and tests. The population used in the study amounted to 30 students. The sample for this research was taken in two classes determined by a simple random sampling technique; each class consisted of 15 students. Test forms and questionnaires are used as data collection instruments. The data analysis technique used is inferential statistics. The study results show the effect of using the Guided Note Taking method assisted by video media on science learning outcomes in the era of society 5.0. it was concluded that using the Guided Note Taking method assisted by video media could improve the learning outcomes of elementary school students. This research implies that teachers in science learning can apply the Guided Note Taking approach assisted by video media to increase students' interest in education and impact student learning outcomes.